2010
DOI: 10.1186/1471-2474-11-159
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and radiographic outcomes of the treatment of adolescent idiopathic scoliosis with segmental pedicle screws and combined local autograft and allograft bone for spinal fusion: a retrospective case series

Abstract: BackgroundHigh morbidity has been reported with iliac crest bone graft harvesting; however, donor bone is typically necessary for posterior spinal fusion. Autograft bone combined with allograft may reduce the morbidity associated with iliac crest bone harvesting and improve the fusion rate. Our aim in this study was to determine the presence of complications, pseudarthrosis, non-union, and infection using combined in situ local autograft bone and freeze-dried cancellous allograft bone in patients undergoing po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 19 publications
(23 reference statements)
0
5
0
Order By: Relevance
“…In this respect, the results of the present study are intriguing. However, it would be premature to arrive at the conclusion regarding the effect of CAFG on bone fusion, because the present study is based on the analysis of implant failure detected on plain radiography similar to previous studies instead of directly assessing bone fusion on CT 30,31) . Although CT is widely accepted as the gold standard for the assessment of bone fusion, it is not recommended to routinely take CT for the assessment of bone fusion, especially in young patients following fusion surgery for idiopathic scoliosis, because CT inevitably causes high radiation exposure in patients 21) .…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, the results of the present study are intriguing. However, it would be premature to arrive at the conclusion regarding the effect of CAFG on bone fusion, because the present study is based on the analysis of implant failure detected on plain radiography similar to previous studies instead of directly assessing bone fusion on CT 30,31) . Although CT is widely accepted as the gold standard for the assessment of bone fusion, it is not recommended to routinely take CT for the assessment of bone fusion, especially in young patients following fusion surgery for idiopathic scoliosis, because CT inevitably causes high radiation exposure in patients 21) .…”
Section: Discussionmentioning
confidence: 99%
“…In 2004, Violas et al [ 7 ] first proposed using only local autologous bone graft in AIS posterior fusion with pedicle screw instrumentation and reported good outcomes. In addition, Yang et al [ 16 ] reported the combination of local autologous bone graft and allograft yielded no failure of fusion in AIS patients receiving posterior fusion with pedicle screw instrumentation. In AIS surgery, local autologous bone graft has been shown to achieve comparable fusion results to iliac crest bone graft in the past 10 years, and has been recommended for the optimal surgical care of patients undergoing AIS [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Less loss of correction was described in patients undergoing pedicle screw system compared with those undergoing Cotrel-Dubousset or Harrington instrumentation (1.1 vs. 5.9 or 6.5°, respectively). [ 15 ]…”
Section: A Llograftmentioning
confidence: 99%